The Role of Various Laboratory Parameters and Imaging Associated with Obstructive Jaundice in Cholangiocarcinoma - Sri Suryo Adiyanti; Rustadi Sosrosumihardjo (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2014)
Cholangiocarcinoma is the second most common primary liver malignancy with a global increase ofincidence and mortality. The mean age at presentation is 50 years. Patients with cholangiocarcinoma usuallywill have symptoms of obstructive jaundice followed with supporting laboratory and imaging findings. Thepredominant clinical feature of extrahepatic cholangiocarcinoma is biliary obstruction resulting in jaundice; while intrahepatic cholangiocarcinoma causes symptoms of intrahepatic mass including abdominal pain in right upper quadrant and other tumor-related symptoms such as cachexia and malaise. The diagnosis and stagingof cholangiocarcinoma require multidisciplinary approaches including laboratory, radiological, endoscopicapproaches and analysis on pathology. This case report describes a patient with a cholangiocarcinoma based on results of endoscopic retrogradecholangiopancreatography (ERCP) imaging. In addition to a diagnosis tool, ERCP can also be a therapeuticmodality for placing stent to reduce symptoms of cholestasis. There were supporting laboratory findings suchas increased bilirubin level, alkaline phosphatase (ALP) and gamma glutamyltransferase (GGT) levels as wellas increased level of tumor markers such as carcinoembryonic antigen (CEA), carbohydrate antigen (CA) 19-9and cytological examination.Keywords: cholangiocarcinoma, jaundice, obstructive, ERCP ABSTRAKKolangiokarsinoma merupakan keganasan hati primer kedua yang paling umum, dimana insiden danmortalitasnya meningkat secara global. Usia rata-rata timbulnya gejala adalah 50 tahun. Pasien dengankolangiokarsinoma pada umumnya mengalami gejala ikterus obstruktif disertai dengan hasil laboratoriumdan pencitraan yang mendukung. Gambaran klinis yang predominan dari kolangiokarsinoma ekstrahepatik adalah obstruksi bilier yang menyebabkan ikterus, sedangkan kolangiokarsinoma intrahepatik menimbulkan gejala adanya massa intrahepatik yang menyebabkan nyeri kuadran kanan atas abdominal dan gejala terkaittumor lainnya yaitu kakeksia dan malaise. Diagnosis dan staging kolangiokarsinoma memerlukan pendekatanmultidisipliner antara lain laboratorium, radiologis, endoskopi dan analisis patologi.Pada kasus berikut ini seorang pasien didiagnosa kolangiokarsinoma yang ditegakkan berdasarkan pencitraanendoscopic retrograde cholangiopancreatography (ERCP). Selain untuk diagnosis, ERCP menjadi modalitasterapi dengan dilakukan pemasangan stent untuk mengurangi gejala kolestasis. Pemeriksaan laboratoriumyang mendukung antara lain peningkatan bilirubin, alkalin fosfat dan gamma glutamil transferase (GGT),peningkatan penanda tumor seperti carcinoembryonic antigen (CEA), carbohydrate antigen (CA) 19-9, dan pemeriksaan sitologi.Kata kunci: kolangiokarsinoma, ikterus, obstruktif, ERCP